The role of enteric dysbacteriosis and modulation of gut microbiota in the treatment of inflammatory bowel disease. (April 2022) - Niu, Wei; Yang, Fuyan; Fu, Ziwei; Dong, Yuelin; Zhang, Zhenhai; Ju, Jianming
Abstract: The incidence of inflammatory bowel disease (IBD) is globally increasing. This disorder seriously affects the quality of life in patients. Interestingly, studies have detected that the intestinal flora imbalance is a critical factor in the progression of IBD. One potential treatment strategy for IBD involves regulating the composition and function of the intestinal flora. To date, a multitude of experiments have confirmed the relationship between intestinal flora, immune regulation, and anti-inflammation. The intestinal flora can reduce intestinal inflammation by regulating immunity and increasing the secretion of metabolic short-chain fatty acids. In this review, we discuss the composition and function of the intestinal flora, the relationship between the intestinal flora and the host, the role of intestinal flora disorders in IBD, and the progress in IBD treatment. Combining the regulation of the intestinal flora with probiotics treatment is considered a promising strategy for substantially improving the treatment of IBD. Highlights: Inflammatory bowel disease (IBD) is a global disease with a high incidence. The intestinal flora imbalance results in the progression of IBD with high probability. Combining the regulation of the intestinal flora with probiotics treatment is a promising strategy for substantially improving the treatment of IBD.